Preparing a measurement for the level of aspiration among students of Physical Education college – university of Baghdad , and its application - Hazza , Abdullah; Abdul Aziz, Tomader (Journal of Physical Education, 2023)
The study aims at Preparing a measurement of the aspiration level among male students and female students to acquire a know ledge of the aspiration level of the sample used in the research and the differences in the level of aspiration among male and female students of the most important ranges of aspiration according to the outlook of both male and female students.The two researchers used the descriptive method in the surveying device the sample of the research contains (270 )male students and(9)female students in% 36,62 from the society of the research chosen from students in the physical Education college in the university of Baghdad.The two researchers prepared the measurement made of 46 items distribute on five spaces .the validity and the reliability were founded by using the statistical method for sociological sciences (Spss).One of the most important deduction of the research is finding a raise in the aspiration level of the sample and the differences in the level according to its field and the absence of morale differences between male students and female students in the aspiration level.The researchers suggested many instructions;its most important suggestion are :paying attention for students aspiration and goals by sport principals and bring to light the positive and realistic and to make more similar students in the university students milieu